Pengaruh Nilai Tukar Rupiah Dan Harga Terhadap Ekspor Karet Alam Di Indonesia Tahun 2017 - 2021 - Anisa Arizona Bandi; Suhenda Suhenda; Gusti Ayu Putu Pristiani (JAMBIS : Jurnal Administrasi Bisnis, 2023)
Indonesian natural rubber is one of the commodities in the agricultural sector that has superior export value so that it contributes more to Indonesia’s foreign exchange earnings. This study aims to determine and analyze the effect of the rupiah exchange rate and prices on natural rubber export in Indonesian for the periode 2017-2021 per month. The type of research used is quantitative research. The data used are time series in the form secondary data obtained from relevant agencies such as the Indonesian Central Statistics Agency, Bank Indonesian (BI) and UN comtrade. The analysis technique used is multiple linear regression analysis from the research that has been done, it shows that : 1) The exchange rate of the rupiah against the United States dollar had a negative and significant effect on Indonesia’s natural rubber export. 2) Rubber price have a negative and significant effect on Indonesia’s natural rubber exports. 3) The exchange rate snd price have a significant simultaneous effect on Indonesia’s natural rubber exports.